Assessment of bringing in the progressive income taxation in Lithuania - Melnykaitė, Monika; Ramanauskaitė, Agnė (Buhalterinės apskaitos teorija ir praktika, 2013)
Lately discussions of bringing in the progressive income taxation in Lithuania are increasing. Consensus on this issue in the society is not reached, thus this article aims to reveal the need for the reform of direct taxation in the Republic of Lithuania and to consider aspects of the project of proposed input of the progressive income tax rate and possible consequences of implementing. The aim of the research is to assess the need and initiatives of bringing in the progressive income taxation in Lithuania. This paper describes the theoretical basis for progressive taxation and discloses the need for the reform of direct taxation in the Republic of Lithuania; and assesses the aspects of the project of proposed input of the progressive income tax rate in Lithuania as well as compares them with other countries in the European Union. The results of the research. It is found that the bringing in the progressive income tax rate should be properly reasoned, and the system of the progressive tax rate establishment should be based on calculations and empirical studies; because it can have both positive (short-term) and negative (long-term) impact on the national economy. After the comparison of the proposed system of the progressive tax rate establishment in Lithuania with systems in other countries of the European Union it was revealed that the Lithuanian one could be improved. The main disadvantage of this system is that it does not reduce the payable income tax of lower-income people. Based on the results of the calculations it was established that in order to improve the system of Lithuania it should be taken into the account the system of United Kingdom. Because it is simple and easy to understand, and the government gets the opportunity to correct the non-taxable amount and income ranges according to the tendencies of economic ratios.